Topical Application of Loperamide/Oxymorphindole, Mu and Delta Opioid Receptor Agonists, Reduces Sensitization of C-fiber Nociceptors that Possess NaV1.8. (15th October 2020) - Uhelski, Megan L.; Bruce, Daniel; Speltz, Rebecca; Wilcox, George L.; Simone, Donald A.
Highlights: Topical application of a combination of loperamide (Lo) and oxymorphindole (OMI) produces potent anti-hyperalgesia. We determined the effects of Lo/OMI combination on responses of C-fiber nociceptors that possess the Nav 1.8 sodium channel. Topical application of Lo/OMI decreased responses of C-fiber nociceptors evoked by blue light and mechanical stimulation. Abstract: It was recently shown that local injection, systemic administration or topical application of the peripherally-restricted mu-opioid receptor (MOR) agonist loperamide (Lo) and the delta-opioid receptor (DOR) agonist oxymorphindole (OMI) synergized to produce highly potent anti-hyperalgesia that was dependent on both MOR and DOR located in the periphery. We assessed peripheral mechanisms by which this Lo/OMI combination produces analgesia in mice expressing the light-sensitive protein channelrhodopsin2 (ChR2) in neurons that express NaV 1.8 voltage-gated sodium channels. These mice ( NaV 1.8-ChR2 + ) enabled us to selectively target and record electrophysiological activity from these neurons (the majority of which are nociceptive) using blue light stimulation of the hind paw. We assessed the effect of Lo/OMI on nociceptor activity in both naïve mice and mice treated with complete Freund's adjuvant (CFA) to induce chronic inflammation of the hind paw. Teased fiber recording of tibial nerve fibers innervating the plantar hind paw revealed that the Lo/OMI combination reduced responses to light stimulation in naïve mice and attenuated spontaneous activity (SA) as well as responses to light and mechanical stimuli in CFA-treated mice. These results show that Lo/OMI reduces activity of C-fiber nociceptors that express NaV 1.8 and corroborate recent behavioral studies demonstrating the potent analgesic effects of this drug combination. Because of its peripheral site of action, Lo/OMI might produce effective analgesia without the side effects associated with activation of opioid receptors in the central nervous system.